Illgraben topographic datasets 2018 - 2021 - de Haas, Tjalling (Utrecht University, 2022)
Topographic data of the Illgraben channel from November 2018 to September 2021. The folder contains orthophotos, DTMs, and hillshades DTMs in geotiff format, and point clouds in .laz format. Models have been made through structure-from-motion with aerial drone images.

There is a new version (1.2) of this dataset, which can be found here; https://public.yoda.uu.nl/geo/UU01/XXASOM.html
Keywords: Natural Sciences - Earth and related environmental sciences (1.5); Illgraben; debris flow; erosion; entrainment; deposition